SARS‐CoV‐2‐specific humoral and cellular immunity in two renal transplants and two hemodialysis patients treated with convalescent plasma. Issue 5 (9th February 2021) - Lindemann, Monika; Krawczyk, Adalbert; Dolff, Sebastian; Konik, Margarethe; Rohn, Hana; Platte, Maximillian; Thümmler, Laura; Schwarzkopf, Sina; Schipper, Leonie; Bormann, Maren; van de Sand, Lukas; Breyer, Marianne; et al.
Highlights: After treatment with convalescent plasma we observed an increase of specific humoral and cellular immunity in two kidney transplant recipients and two haemodialysis patients with SARS‐CoV‐2 infection. However, the success of convalescent plasma therapy was only be temporary in one transplant recipient. Short‐term monitoring of viral load and antiviral immunity appears as mandatory for this patient group. Abstract: When patients with chronic kidney disease are infected with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) they can face two specific problems: virus‐specific immune responses may be impaired and remdesivir, an antiviral drug described to shorten recovery, is contraindicated. Antiviral treatment with convalescent plasma (CP) could be an alternative treatment option. In this case report, we present two kidney transplant recipients and two hemodialysis patients who were infected with SARS‐CoV‐2 and received CP. Antibodies against the receptor‐binding domain in the S1 subunit of the SARS‐CoV‐2 spike protein were determined sequentially by immunoglobulin G (IgG) enzyme‐linked immunosorbent assay (ELISA) and neutralization assay and specific cellular responses by interferon‐gamma ELISpot. Before treatment, in both kidney transplant recipients and one hemodialysis patient antibodies were undetectable by ELISA (ratio < 1.1), corresponding to low neutralizing antibody titers (≤1:40). ELISpot responses in the four patients were either weak or absent. After CP treatment, we observed an increase of SARS‐CoV‐2‐specific antibodies (IgG ratio and neutralization titer) and of specific cellular responses. After intermittent clinical improvement, one kidney transplant recipient again developed typical symptoms on Day 12 after treatment and received a second cycle of CP treatment. Altogether, three patients clinically improved and could be discharged from the hospital. However, one 83‐year‐old multimorbid patient deceased. Our data suggest that the success of CP therapy may only be temporary in patients with chronic kidney disease; which requires close monitoring of viral load and antiviral immunity and possibly an adaptation of the treatment regimen.